Development of Unified High-Fidelity Flight Dynamic Modeling Technique for Unmanned Compound Aircraft - Do hyeon Lee; Chang-joo Kim; Seong han Lee (International Journal of Aerospace Engineering)
This study presents the unified high-fidelity flight dynamic modeling technique for compound aircraft. The existing flight dynamic modeling technique is absolutely depended on the experimental data measured by wind tunnel. It means that the existing flight dynamic model cannot be used for analyzing a new configuration aircraft. The flight dynamic modeling has to be implemented when a performance analysis has to be performed for new type aircraft. This technique is not effective for analyzing the performance of the new configuration aircraft because the shapes of compound aircraft are very various. The unified high-fidelity flight dynamic modeling technique is developed in this study to overcome the limitation of the existing modeling technique. First, the unified rotor and wing models are developed to calculate the aerodynamic forces generated by rotors and wings. The revolutions per minute (RPM) and pitch change with rotation direction are addressed by rotor models. The unified wing model calculates the induced velocity by using the vortex lattice method (VLM) and the Biot–Savart law. The aerodynamic forces and moments for wings and rotors are computed by strip theory in each model. Second, the performance analysis such as propeller performance and trim for compound aircraft is implemented to check the accuracy between the proposed modeling technique and the helicopter trim, linearization, and simulation (HETLAS) program which is validated. It is judged that this study raises the efficiency of aircraft performance analysis and the airworthiness evaluation.